PERSEPSI MASYARAKAT MUSLlM TENTANG ZAKAT DI KOTA PALU - Attamimi, Faisal (State Institute of Islamic Studies (IAIN) Palu, 2008)
The purpose of this study was to analyze the perception of Muslim society of Palu to dhakâh. The method employed in this reserach was qualitative one. The teachniques of data collection employed was observation, interview and questionaire. The results of this research indicated that most of Muslims of Palu percieved dhakâh as being an indivudual ibâdah so that they preferred distributing their dhakâh individually to distributing it through the BAZ (The Office of Collector and Distributor of Alms-Giving). The BAZ of Palu could not be optimally managed because of (1) the lack of human resources; (2) the lack of Muslims’ knowledge of Palu about the essence of dhakâh, and (3) the ineffectiveness of dhakâh management of the BAZ of Palu.Kata Kunci: persepsi, masyarakat muslim, zakat, Badan Amil Zakat